Pandangan Filosofis Tentang Hakikat Lingkungan Alam Sebagai Landasan Pendidikan Islam - Muhaimin; Tarwilah; Suraijiah (Advances In Education Journal, 2026)
The current environmental crisis is not merely ecological in nature but also reflects a crisis of human values and spirituality. Islam views the natural environment as an ayah of Allah that possesses theological, ethical, and spiritual significance, and therefore should serve as a foundational element in Islamic education. This study aims to examine the philosophical perspective of Islam on the nature of the environment and to analyze its relevance as a foundation for Islamic education. The research employs a qualitative approach using library research methods by collecting data from the Qur’an, classical tafsir works, and relevant scholarly books and journal articles. The findings indicate that Islam positions humans as khalifah entrusted with the responsibility of maintaining ecological balance, while emphasizing the integration of tarbiyah, ta’dib, and ta‘lim in cultivating ecological awareness. This study concludes that environmental education grounded in Islamic values plays a crucial role in fostering sustainable ecological and spiritual character development among learners.